Technology acceptance model based study of students’ attitudes toward use of enterprise resource planning solutions - Sternad, Simona, ekonomistica (Array, 2019)
Enterprise Resource Planning (ERP) solutions are the most frequently used software tool in companies in all industries. Therefore, the labour market requires the knowledge and skills for usage of ERP solutions from graduates – future employees. The main objective of our paper is therefore the identification of important factors that contribute to the acceptance of ERP solutions by students in economics and business and that shape their intentions to use this knowledge in the future. The model of our research is based on the Technology Acceptance Model (TAM), extended by identified important multidimensional external factors that refer to (1) students’ personal characteristics and information literacy, (2) perceived system and technological characteristics of ERP solutions and (3) perceived support within the study process. Research results revealed that several dimensions of the three multidimensonal factors play an important role in shaping the attitudes towards acceptance of ERP solutions by students.